Cup of gold : a life of Sir Henry Morgan, Buccaneer, with occasional reference to history ... - Steinbeck, John, 1902-1968. (New York : Penguin Books, 1976)
Devoured by lust and greed, Morgan still had two ambitions: to possess the mysterious woman known as La Santa Roja and to conquer Panama.
Reprint of the ed. published by McBride.
Adult
Adult
Keywords: Morgan, Henry, -- Sir, -- 1635?-1688 -- Fiction; Governors -- Jamaica -- Fiction; Buccaneers -- Fiction; Morgan, Henry Sir, 1635?-1688 -- Fiction; Biographical fiction